Dropping out of organized sport or staying in? A prospective study on the influence of psychosocial factors - Ommundsen, Y.; Roberts, G. C.; Miller, B. W.; Sisjord, M. K.; Fasting, K.; Sorensen, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Participation in organized youth sport across childhood and adolescence increase the likelihood of being physically active in adulthood (Telama et al 2006). Hence, preventing young people from dropping out of organized sport may be seen as an important health promotion strategy. Study purpose: To examine the influence of a theoretically informed set of environmental and personal factors on young athletes` dropout from organized sport. Method: Prospective design including a sample of 698 athletes aged 12-16 years from different sports who provided T 1 (early season) data and responses regarding their participation status the following sport season (T 2). T 1 predictors comprised perceptions of the sport environment, cognitive mediators of motivation and persistence, regulation of motivation and affect. Results: Direct logistic regression helped assess the impact of predictor variable set on the likelihood of next season dropout. The full model containing all predictors was statistically significant, X2 (13, N= 678) = 68,23, p<.001, indicating that the model was able to distinguish between athletes who reported and did not report having dropped out of organized sport. The model as a whole explained between 25% (Cox and Snell R square) and 36% (Nagelkerke R squared) of the variance in organized sport participation status, and correctly classified 84% of the cases. Seven predictor variables made a unique statistically significant contribution to the dropout model. The strongest predictors - odds ratios of 2.13 and 1.82 - were a high performance climate and high perceived ability, respectively. Athletes, who early season perceived the climate as strongly performance oriented, were over 2 times more likely to report dropout than those who did not, controlling for all other factors in the model. Further, athletes high on perceived ability were 1.8 times more likely to report dropout than their counterparts. The odds ratios of perceived autonomy and relatedness were less than 1. Hence, for every additional level of agreement in terms of being socially integrated with peers in sport, athletes were .70 times less likely to report dropout, controlling for other factors in the model. Finally, boys were .60 times less likely to dropout of sport than were the girls, and younger athletes were .59 times less likely to dropout than older ones. Discussion: Results reveal the importance of de-emphasizing social comparison and winning while simultaneously strengthening athletes` sense of autonomy and social bonds with their sport peers, and prevent negative affect. Findings also reveal that preventing dropout seem particularly important among girls